SHEFEX-2 - Development Status of the Vehicle and Sub-Systems for a Hypersonic Re-Entry Flight Experiment - Turner, John; Hörschgen, Marcus; Ettl, Josef; Jung, Wolfgang; Turner, Peter (2009)
The SHarp Edge Flight EXperiment (SHEFEX) is a DLR program to investigate aerodynamic behaviour and thermal protection problems of re-entry vehicles at hypersonic velocities, using unconventional shapes comprising multi-facetted surfaces with sharp edges. SHEFEX 1 was launched on a parabolic trajectory from Andøya Rocket Range in 2005 to provide a re-entry velocity in the order of Mach 7. To obtain greater velocities in the order of Mach 10, without reducing the experiment time, a larger vehicle and a flatter re-entry trajectory are required. A Brazilian VS40 motor system will be used, whereby the S40 first stage will provide a conventional spin stabilized unguided flight, but a pitch down precession manoeuvre of the S44 second stage will be performed prior to its ignition above the atmosphere. This will result in a suppressed trajectory and a re-entry angle of the order of 40 degrees. In addition to the thermal protection experiments, a canard system will provide data on the aerodynamic control parameters at hypersonic velocities. A further experiment comprises a separate inertial navigation system with a star reference update and GPS, which should determine the instantaneous flight vector and provide fine corrections to the main payload attitude control system to reduce any angle of attack inaccuracy.